Optimizing the Role of Benowo PLTSA in the Step of Energy Mitigation and Transition to Net Zero Emission - AFFANDI, Fajar Gunawan; FAHMI, Ice; SASONGKO, Nugroho Adi; YOESGIANTORO, Donny; PANDEY, Fhandy (International Journal of Environmental, Sustainability, and Social Science, 2024)
Every human being always produces waste in his life, be it organic waste or inorganic waste. With the increasing number of people in the world, of course, the amount of waste produced will increase. To overcome these problems, we need a technology that can utilize waste to be used as a source of renewable energy, as was done by PLTSa Benowo in the city of Surabaya. At PLTSa Benowo, the use of waste to be used as a renewable energy source is carried out in two ways, namely Landfill Gas Recovery (LFG) and Gasification. The two processes will produce gas which will be used to generate 11 MW of electrical energy. Utilization of waste to be used as a source of electrical energy provides many benefits for humans, besides being able to overcome the problem of urban waste which is increasingly piling up, it can also provide electricity supply for PLN. The author uses descriptive methods through a qualitative approach, this research intends to understand what phenomena are experienced by the research subjects. The results of the research are expected to provide additional knowledge about PLTSa Benowo which is located in the city of Surabaya.